2015
DOI: 10.5935/1984-6835.20150092
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials Applied as Electrocatalysts in the Oxidation Reaction of Ethanol

Abstract: Abstract:Electrocatalyst containing platinum supported on high surface area carbon Vulcan XC-72 were synthesized by the method of reduction by alcohol and tested in comparison to ethanol oxidation reaction in acidic medium. The materials studied were Pt/C 20%, Pt 80 Ir 20 /C, Pt 80 W 20 /C, Pt 80 Sn 20 /C and Pt 60 Ir 10 Sn 30 /C, using as a standard for comparison the commercial catalyst Pt/C 20% E-TEK. Physical characterization was performed using energy dispersive (EDX), X-ray diffraction (XRD), Transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…For example, the preparation of catalysts with core-shell structure with the following composition SnO 2 @Pt/C, Ni@Pt/C and NiSn@Pt/C 12 and catalysts with distinct compositions Pt/C, Pt 80 Ir 20 /C, Pt 80 W 20 /C, Pt 80 Sn 20 /C and Pt 60 Ir 10 Sn 30 /C. 13 The addition of a second metal such as cobalt (Co), manganese (Mn) and cadmium (Cd) to a nickel-based catalyst increases the catalytic activity of this metal in the process of the electro-oxidation reaction of urea. 14 Additionally, in a previous publication of our research group, it was shown that the addition of a lower amount of platinum to nickel catalysts (Ni 95 Pt 5 /C and Ni 90 Pt 10 /C) results in an enhancement in the catalytic activity towards urea electro-oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the preparation of catalysts with core-shell structure with the following composition SnO 2 @Pt/C, Ni@Pt/C and NiSn@Pt/C 12 and catalysts with distinct compositions Pt/C, Pt 80 Ir 20 /C, Pt 80 W 20 /C, Pt 80 Sn 20 /C and Pt 60 Ir 10 Sn 30 /C. 13 The addition of a second metal such as cobalt (Co), manganese (Mn) and cadmium (Cd) to a nickel-based catalyst increases the catalytic activity of this metal in the process of the electro-oxidation reaction of urea. 14 Additionally, in a previous publication of our research group, it was shown that the addition of a lower amount of platinum to nickel catalysts (Ni 95 Pt 5 /C and Ni 90 Pt 10 /C) results in an enhancement in the catalytic activity towards urea electro-oxidation.…”
Section: Introductionmentioning
confidence: 99%